1997
DOI: 10.1111/j.1525-1594.1997.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blood Flow on Adsorption of β2‐Microglobulin onto AN69 Membrane

Abstract: Adsorption onto the dialyzer membrane is a contributing factor to the elimination of P,-microglobulin (P,M) from the sera of uremic patients. The purpose of this prospective study was to ascertain the influence of the blood flow rate on adsorption of P2M onto the polyacrylonitrile (AN69) hollow-fiber dialyzer membrane in 8 patients during regular hemodialysis (HD). Blood first passed through a low-flux polysulfone dialyzer and then through an AN69 dialyzer, which was not in contact with the dialysis fluid. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The present or related studies have suggested that saturation of an immunoadsorption process could be completed within a relatively short period of time (16). On the other hand, the removal of β‐2M is primarily dependent on the available adsorption surface but is independent of the blood flow rate (34,35). Thus, for a blood flow‐circuit as shown previously (14), the blood flow rate could be tentatively maintained as that in the hemodialyzer but immunoadsorption procedure could be performed in less time than hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…The present or related studies have suggested that saturation of an immunoadsorption process could be completed within a relatively short period of time (16). On the other hand, the removal of β‐2M is primarily dependent on the available adsorption surface but is independent of the blood flow rate (34,35). Thus, for a blood flow‐circuit as shown previously (14), the blood flow rate could be tentatively maintained as that in the hemodialyzer but immunoadsorption procedure could be performed in less time than hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…More than 70% of 615,000 end stage renal disease patients are on dialysis in America. 1 Although several types of hollow fiber dialysis membranes which eliminating uremic toxins though diffusion process are used in clinics, [2][3][4][5] the dialysis process is still inconvenient, time consuming, and expensive.…”
Section: Introductionmentioning
confidence: 99%